2018
DOI: 10.2174/1389557517666170913111533
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacophore Comparison and Development of Recently Discovered Long Chain Arylpiperazine and Sulfonamide Based 5-HT7 Ligands

Abstract: The serotonin system exerts its effects on the CNS and many peripheral systems. Of the 14 serotonin receptors, the 5-HT7 receptor is the most recently discovered. The 5-HT7 receptor has been shown to be involved in stress reduction, depression, and nociceptive control. Despite the 20 years since the discovery of 5-HT7R, there are still few truly selective ligands. Two of the common scaffolds for 5-HT7R ligands are long chain arylpiperazines (LCAPs) and sulfonamide containing compounds. This review focuses on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…The obtained results indicated that two different solvates were formed. Interestingly, the 15 Knowing that two different solvates, 1-MeOH and 1-EtOH, are formed, we focused on obtaining high-quality single crystals. In both cases, we obtained good enough crystals to perform scXRD experiments (Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The obtained results indicated that two different solvates were formed. Interestingly, the 15 Knowing that two different solvates, 1-MeOH and 1-EtOH, are formed, we focused on obtaining high-quality single crystals. In both cases, we obtained good enough crystals to perform scXRD experiments (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…The NMR experiments were performed using cross-polarization (CP), high-power decoupling, and magic-angle spinning (MAS) using a Bruker 4.0 mm HX CP/MAS probe with zirconia rotors driven by dry air. The spin rates of 8 kHz and 5 kHz for 13 C and 15 N NMR experiments were used, respectively. The Hartmann-Hahn conditions for 13 C and 15 N were matched using glycine 15-N.…”
Section: Solid-state Nuclear Magneticmentioning
confidence: 99%
See 2 more Smart Citations
“…Since it was discovered in 1993, there has been extensive research into its role in the central nervous system. 10 In addition to its wellestablished role in cognition, 11 circadian rhythms 12 and depression, 13 its involvement in various cancers has also been reported. [14][15][16][17][18] Although the 5-HT 7 receptor has been implicated in many lung-associated pathologic processes in rats 19,20 and guinea-pigs, 21,22 research on the 5-HT 7 receptor in human lungs is limited.…”
Section: Introductionmentioning
confidence: 99%